Strengthening Prosecutor’s Commission in Indonesia - Priharyadi, Nanang Dwi; Pujiyono,; Purwadi, Hari (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to analyze the urgency of strengthening the Prosecutor's Commission in order to be able to foster a credible institution through the performance of professional prosecutors. The strengthening referred to the improving regulations and policies. The research method used is normative, with legal material consits of regulations, books, journals and various supporting literatures. The analysis was carried out qualitatively. The results show that the tasks carried out by the prosecutorial commission in terms of supervision, monitoring and evaluation of the professional performance of the prosecutor's apparatus had not been effective, because of the limited authority of the prosecutorial commission which was limited to providing recommendations and proposals. Therefore, in order for the prosecutorial Commission's recommendations to be implemented, it must routinely coordinate and communicate with the prosecutor's internal oversight unit, in addition to improving regulations with giving executorial powers also needed.